Spectral Characterization, Antioxidant and Antibacterial Activities of Cold Methanolic Extract of Sweet Basil (Ocimum basilicum L.) Leaves Growing in Jazan, Kingdom of Saudi Arabia - Alam, Md Shamsher; Albratty, Mohammed; Hassan Ahmed, Hassan Ahmed; Najmi, Asim; Zoghebi, Khalid; Rehman, Zia ur; Basode, Vinod Kumar; Moni, Sivakumar S.; Alam, Mohammad Firoz; Ahsan, Waquar; Kochikuzhyil, Benson Mathai (Indian Journal of Pharmaceutical Education and Research, 2024)
Background This study evaluated the chemical composition, antioxidant activity and antibacterial properties of methanol extracts of Ocimum basilicum L. leaves that were gathered from the Kingdom of Saudi Arabia’s Jazan province. Materials and Methods The extract was examined using FTIR and GC-MS techniques, which revealed the presence of terpenes (53.14%), Linalool (24.5%), sulfoxides (4.19%), cinnamic acid (5.23%), fatty acid esters (1.45%) and phthalic acid esters (0.72%). Results The extract contained significant levels of total phenolic compounds and demonstrated a DPPH radical scavenging capacity of 33.70%, which is considered to be good. The antibacterial activity spectrum of O. basilicum leaves’ methanolic extract was found to be broader. The extract was tested against eight different bacteria strains, including S. cholestasis, S. aureus, S. epidermidis, K. pneumoniae, E. coli, P. mirabilis, E. faecalis, and S. cholestasis. Conclusion With an inhibition zone of 21 mm, S. aureus exhibited the highest level of antibacterial activity, whereas P. aeruginosa demonstrated the lowest value, with an inhibition zone of 15 mm. Nonetheless, the activity range was more constrained than that of regular ciprofloxacin discs.
Keywords: Ocimum basilicum; Sweet Basil; Ftir Spectroscopy; GC-MS; Antioxidant Activities; Antibacterial Activities